Changes of Colorectal Cancer Diagnostics and Hospitalizations during First Wave of COVID-19 Pandemic in Lithuania - Jurkevičiūtė, Dignė; Mauravičiūtė, Sandra; Dulskas, Audrius; Kildušienė, Inga; Stratilatovas, Eugenijus; Jarmalaitė, Sonata (Acta medica Lituanica, 2023)
Purpose: Our aim was to see the possible effect of the first COVID pandemic wave in Lithuania on colorectal cancer (CRC) preventive, diagnostic and treatment procedures.Methods: A retrospective analysis was performed using the database of the National Cancer Institute, Lithuania. We have divided patients into two groups: group 1 – patients treated during the nonpandemic period (2019 January 1 to 2019 July 31) and group 2 – the pandemic period (2020 January 1 to 2020 July 31). We analyzed numbers of screening, therapeutic colonoscopies performed, and treated patients for CRC during two periods.Results: In general, 1318 lower gastrointestinal endoscopic procedures were performed in the first group and 862 procedures in the second group, which was 34.6% less compared to the first group. The first group included 672 (51%) colonoscopies, 172 (13%) day surgeries and 474 (36%) CRC screening programmes. In group 2, 456 (34.6%) less patients underwent CRC diagnostics and treatment: 141 (21%) less colonoscopies, 93 (54%) less day surgeries, 222 (47%) less CRC screening programmes, and 26 (13%) less patients were hospitalized for surgical treatment (196 vs 170).Conclusion: Our study reveals worrying changes in the timely access to diagnostic procedures during the COVID-19 pandemic that possibly provoked rise in cases with the advanced stage CRC. However, despite numerical difference between groups existed, the difference between groups do not reach statistical significant level.
Keywords: COVID-19 pandemic; colorectal cancer; colorectal cancer screening; short-term results